2021
DOI: 10.1021/acs.analchem.1c02347
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Automated Annotation and Analysis of N-Glycan Mass Spectrometry Imaging Data Sets Using NGlycDB in METASPACE

Abstract: Imaging N-glycan spatial distribution in tissues using mass spectrometry imaging (MSI) is emerging as a promising tool in biological and clinical applications. However, there is currently no high-throughput tool for visualization and molecular annotation of N-glycans in MSI data, which significantly slows down data processing and hampers the applicability of this approach. Here, we present how METASPACE, an open-source cloud engine for molecular annotation of MSI data, can be used to automatically annotate, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…To obtain maximal coverage of N -glycans from the soybean root nodules, we tested and compared commercially available recombinant PNGaseF PRIME that has been widely used in N -glycan MALDI-MSI of mammalian tissues (Powers et al, 2014 ; Carter et al, 2020 ; Blaschke et al, 2021 ; Mcdowell et al, 2021 ) and acidic PNGase H+ that has previously shown high specificity in bulk plant N -glycan profiling (Du et al, 2015 ). For assessing their efficiency, we concurrently sprayed these enzymes over the cross-section of wild type and nifH - FFPE soybean root nodule, analyzed released glycans by MALDI-MSI, and automatedly annotated N -glycans using the NGlycDB (Velickovic et al, 2021 ) in METASPACE. METASPACE is an open cloud software platform that performs molecular annotations for MSI data—based not only on the accurate mass information but also on a comprehensive bioinformatics framework that considers the relative intensities and spatial colocalization of isotopic peaks, as well as quantifies spatial information with a measure of spatial chaos followed by the estimation of the False Discovery Rate (FDR) (Palmer et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To obtain maximal coverage of N -glycans from the soybean root nodules, we tested and compared commercially available recombinant PNGaseF PRIME that has been widely used in N -glycan MALDI-MSI of mammalian tissues (Powers et al, 2014 ; Carter et al, 2020 ; Blaschke et al, 2021 ; Mcdowell et al, 2021 ) and acidic PNGase H+ that has previously shown high specificity in bulk plant N -glycan profiling (Du et al, 2015 ). For assessing their efficiency, we concurrently sprayed these enzymes over the cross-section of wild type and nifH - FFPE soybean root nodule, analyzed released glycans by MALDI-MSI, and automatedly annotated N -glycans using the NGlycDB (Velickovic et al, 2021 ) in METASPACE. METASPACE is an open cloud software platform that performs molecular annotations for MSI data—based not only on the accurate mass information but also on a comprehensive bioinformatics framework that considers the relative intensities and spatial colocalization of isotopic peaks, as well as quantifies spatial information with a measure of spatial chaos followed by the estimation of the False Discovery Rate (FDR) (Palmer et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…METASPACE is an open cloud software platform that performs molecular annotations for MSI data—based not only on the accurate mass information but also on a comprehensive bioinformatics framework that considers the relative intensities and spatial colocalization of isotopic peaks, as well as quantifies spatial information with a measure of spatial chaos followed by the estimation of the False Discovery Rate (FDR) (Palmer et al, 2017 ). Recently, we introduced NGlycDB which contains naturally occurring N -linked glycans, including all reported plant glycans, for researchers worldwide to annotate their spatial N -glycomics using METASPACE (Velickovic et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem is even more emphasized in highly heterogeneous tissues, composed from the spatially close but different cell types (e.g., kidney). For example, reported ion images of released N -glycans in kidney tissue sections can often look “smeared” without distinct, clear, spatial patterns that colocalize with glomeruli or tubular structures. ,, …”
mentioning
confidence: 99%